Non-coding RNAs in Host–Pathogen Interactions: Subversion of Mammalian Cell Functions by Protozoan Parasites - Bayer-Santos, Ethel; Marini, Marjorie M.; da Silveira, José F. (Frontiers in Microbiology, 2017)
Pathogens have evolved mechanisms to modulate host cell functions and avoid recognition and destruction by the host damage response. For many years, researchers have focused on proteins as the main effectors used by pathogens to hijack host cell pathways, but only recently with the development of deep RNA sequencing these molecules were brought to light as key players in infectious diseases. Protozoan parasites such as those from the genera Plasmodium, Toxoplasma, Leishmania and Trypanosoma cause life-threatening diseases and are responsible for thousands of deaths worldwide every year. Some of these parasites replicate intracellularly when infecting mammalian hosts, whereas others can survive and replicate extracellularly in the bloodstream. Each of these parasites uses specific evasion mechanisms to avoid being killed by the host defense system. An increasing number of studies have shown that these pathogens can transfer non-coding RNA molecules to the host cells to modulate their functions. This transference usually happens via extracellular vesicles, which are small membrane vesicles secreted by the microorganism. In this mini-review we will combine published work regarding several protozoan parasites that were shown to use non-coding RNAs in inter-kingdom communication and briefly discuss future perspectives in the field..